2017
DOI: 10.1002/asia.201701048
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Thermal Properties of Polycarbonates/esters Catalyzed by Using Dinuclear Salph‐Al from Ring‐Opening Polymerization of Epoxide Monomers

Abstract: A dinuclear Salph-Al complex/bis(triphenylphosphine)iminium chloride catalyst system was synthesized and employed for cyclohexene oxide (CHO) and CO copolymerization. The catalyst system had an excellent selectivity of 99 % for carbonate linkages and the resultant poly(cyclohexene carbonate) (PCHC) had a high glass transition temperature (T ) of 123.8 °C and a thermal decomposition temperature (5 % weight loss; T ) of 265 °C. Furthermore, this catalyst system was active in the polymerization of phthalic anhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Differential scanning calorimetry (DSC) shows the two blocks are amorphous and only glass transitions are observed (Figures S13–S18). For example, ABA-50 shows two T g values at similar temperatures to the homopolymers ( T g,PDL ≅ −58 °C, T g,PCHC ≅ 110–120 °C , ). Some of the other samples only show the lower T g , by DSC analysis, although in all cases its value is close to −60 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) shows the two blocks are amorphous and only glass transitions are observed (Figures S13–S18). For example, ABA-50 shows two T g values at similar temperatures to the homopolymers ( T g,PDL ≅ −58 °C, T g,PCHC ≅ 110–120 °C , ). Some of the other samples only show the lower T g , by DSC analysis, although in all cases its value is close to −60 °C.…”
Section: Resultsmentioning
confidence: 99%
“…First, we investigated the ROCOP process in the absence of a cocatalyst (Table , entries 1–4), and the results showed that good conversions with low selectivities were obtained. Because previous reports confirmed that adding a nucleophile source as a cocatalyst increased the copolymerization selectivities, the effect of adding tetrabutylammonium bromide (TBAB) as a cocatalyst was studied, showing that selectivities could be improved up to 91% toward the synthesis of the polyester (Table , entries 5–8). Entries 1–8 evidenced that bimetallic complexes 3 – 4 were more active for the ROCOP of CHO and SA than the monometallic counterparts 1 – 2 .…”
Section: Resultsmentioning
confidence: 99%
“… The main drawbacks of this process are still the low molecular weight of the obtained polymers and the modest selectivity of the catalysts tested. In the search of better catalysts for the development of biodegradable architectures, systems based on zinc, cobalt, chromium, and aluminum have been thoroughly studied. Amongst them, aluminum complexes are the most attractive because of its Earth’s crust abundancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, for dinuclear complexes, the addition of cocatalysts can be avoided. Besides, bimetallic catalysts show good catalytic performance due to the synergy between the metal centers (Zhou et al, 2017). The Williams group has prepared a series of dizinc catalysts, including LZn 2 (X) 2 [X = OAc, O 2 CCF 3 , phenyl (Ph)] (Romain and Williams, 2014;Thevenon et al, 2015;Yi et al, 2015;Romain et al, 2017) coordinated by a macrocyclic ligand (Figure 2), which exhibits excellent catalytic efficiency and high selectivity for ROCOP of CO 2 and epoxides at relatively low CO 2 pressure (∼1 bar).…”
Section: Catalyst Systems Homodinuclear Catalystsmentioning
confidence: 99%